Semi-quantitative prioritization based on evidence of zoonotic bacterial diseases present at the interface between wild pigs (Sus scrofa), domestic pigs and humans in Colombia - Martínez-Granados, Natalia (2021)
The aim of this study was to prioritize the zoonotic bacterial diseases present in the interface between wild pigs (Sus scrofa), domestic pigs and humans in Colombia. A review of indexing and abstracting systems and data from the World Animal Health Information System (WAHID/WAHIS) was carried out. The semi-quantitative method of prioritization based on evidence was used with 27 criteria in five categories: epidemiology, prevention/control, economy/trade, public health and society, with values between 0 (no risk) and 7 (severe risk). Salmonellosis (148 points) and tuberculosis (148) presented high zoonotic potential, with evidence of a higher score in epidemiology, public health and society criteria; followed by yersiniosis (140) and brucellosis (127) with medium zoonotic potential, and finally leptospirosis (119) and pasteurellosis (114) with low zoonotic potential.